Fractured indwelling pleural catheters. - Fysh, E; Wrightson, J; Lee, Y; Rahman, N (2012)
Indwelling pleural catheters (IPCs) are increasingly used in the management of malignant pleural effusions. IPCs are designed to be secured in situ indefinitely; however, in selected patients, IPCs can be removed when drainage ceases. This case series reports complications of removal of IPCs that resulted in fractured catheters or necessitated deliberate severing of the catheters. From the combined data of two pleural centers, 61 of 170 IPCs inserted (35.9%) were removed. In six cases (9.8%), the removals were complicated, leading to fracture or iatrogenic severing of the IPC. Although four patients had catheter fragments retained within the pleural space, none developed any complications (eg, pain or infection) (median follow-up, 459 days; range, 113-1,119 days), despite two patients undergoing subsequent chemotherapy. Clinicians should be aware that IPC removal can be problematic, but retained fragments are safe, and aggressive retrieval is unnecessary.